(untitled) (Spandan, 2023)
The present paper deals with Marxist-influenced post-modern constructionism and poststructuralist theories. Then, it problematizes the issues of language, language learning, and language education in Nepal in the light of critical theory. The paper makes a cursory review of the Marxist tradition of language study and connects it with the post-structural and post-modern considerations. It further deals with the existing scenario of language and language education in Nepal and problematizes the expansion of the English language in the cost of language genocide of the mother tongues. The woman with all the cats comes shopping here regularly.